PENDIDIKAN PESANTREN DITENGAH TANTANGAN POLITISASI DAN GLOBALISASI: Pesantren Madura Setelah Keruntuhan Orde Baru - Halik, Fathol (STAIN PAMEKASAN, 2012)
Â Abstrac Globalization, which has been constructed by peasntren, is interesting to observe. It serves economic capitalization, creates transformative-culture and reproduces culture and knowledge. Nowadays, pesantren (kiai) no longer becomes a single institution (agent) of social reality. The starting point of this article is to analyze the education of Madurese pesantren within the politic and globalization streams. The problems that have been purposed are that—how pesantren education set themselves in political and globalization streams? How the peasantren elites give the meaning of politic and globalization? How globalization is